Comparison of Goal Achievement When Transitioning from In-Person Therapy to Teletherapy in the Westchester County Early Intervention Program Due to the COVID-19 Pandemic - Inna C. De Leon; JennaLynn Philipps; Marina Yoegel; Joseph Byrnes; Jordan S. Kase (International Journal of Telerehabilitation, 2022)
The sudden transition to virtual therapeutic services during the COVID-19 pandemic provided a unique opportunity to explore telehealth as a platform for delivering early intervention (EI) services. Through retrospective chart review of 93 children, we collected the following data: demographics, diagnosed conditions, therapy type, service format, and provider-reported participant goal achievement (1=no progress, 2=little progress, 3=moderate progress, 4=great deal of progress, 5=outcome achieved) over a six-month period before and after transitioning to telehealth. Pre- and post-transition progress scores were compared using the Wilcoxon signed-rank test. Results demonstrated maintained progress among children who transitioned from in-person to virtual services for similar therapy types. Children receiving speech therapy in-person and virtually demonstrated increased achievement (3.00 vs 3.33; p=0.032). Participants receiving a particular therapy post-transition but not in-person attained similar achievement as those who received the same therapy only in-person. Our research suggests that teletherapy may be a viable option for delivering EI services.